Wheatgrass extract has chondroprotective and anti-inflammatory effects on porcine cartilage - Cridland, Kate; Garland, Anna; McCrae, Persephone; Pearson, Wendy (Frontiers in Animal Science, 2023)
Lameness is a commonly observed disorder in sows and negatively impacts both animal welfare and the profitability of the pig sector. The purpose of this study was to determine anti-inflammatory and/or chondroprotective effects of wheatgrass (WG) on porcine cartilage explants stimulated with lipopolysaccharide (LPS). Explants were aseptically prepared from the intercarpal joints of nine market-weight pigs and placed in culture at 37°C for a total of 120 hours. For the final 96 hours, explants were conditioned with an aqueous extract of WG (0, 5 or 15 μg/mL), and for the final 48 hours explants were stimulated with LPS (0 or 10 µg/mL). Media was removed and replaced every 24 hours. Samples from the final 48 hours were analyzed for biomarkers of cartilage inflammation [prostaglandin E2 (PGE2) and nitric oxide (NO)] and cartilage structure [glycosaminoglycan (GAG)], and cartilage explants were stained for an estimate of cell viability. Stimulation of explants with LPS significantly increased media concentrations of PGE2, GAG and NO compared with that from unstimulated explants. LPS stimulation did not significantly affect cell viability. Conditioning of explants with WG (5 μg/mL) significantly reduced LPS-stimulated cartilage release of PGE2, NO, and GAG (5 and 15 μg/mL), without impairing chondrocyte viability. These data provide evidence for a non-cytotoxic chondroprotective and anti-inflammatory effect of WG extract in cartilage and suggest a role of WG in protection against cartilage breakdown, inflammation, and pain associated with osteoarthritis.